MEMBER SATISFACTION AMONG MULTIPURPOSE COOPERATIVES: ITS EFFECT ON THE INFLUENCE OF ECONOMIC FACTORS ON COOPERATIVE MEMBER COMMITMENT - Gil-Salapi, Candy Elizabeth (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
Cooperatives are a type of business organization that is owned and controlled democratically by its members. One of the key principles of cooperatives is to prioritize the social and economic well-being of their members and the communities in which they operate. Multipurpose cooperatives in the Philippines are cooperatives that provide a wide range of services to their members, such as credit, savings, insurance, and other services. These also perform the functions of financing and marketing. Moreover, they serve as the savings structure and source of household and agricultural supplies of its members whose capital contribution is the source of the resources of cooperatives in the savings, loans, and marketing sector along with the profit from their credit, marketing, and other economic activities (Perilla et al., 2009). As cooperatives promote economic development and poverty reduction, it is vital that these organizations sustain their operations in order that they will be able to continue these vital roles. One important means by which cooperatives will succeed is for them to develop and nurture commitment among their members (Fulton, 1999). In his study on cooperatives and member commitment in 1999, Fulton defined cooperative member commitment as "the willingness of a member to contribute to the cooperative's success through participation, financial support, and advocacy, and the degree to which that willingness is sustained over time." According to Fulton, member commitment is a critical factor in the success of cooperatives. He argued that highly committed members are more likely to actively participate in the cooperative, contribute financially, and promote the cooperative to others. In contrast, members with low commitment are less likely to participate or support the cooperative, which can hinder its growth and sustainability. He further added that commitment is what differentiates a cooperative from investor-owned firms. The present study assessed the effect of member satisfaction on the influence of economic factors on member commitment among multipurpose cooperatives in Southern Leyte, Philippines. Awoke (2021) refers to member satisfaction as satisfaction of the members in the performance of the cooperatives. Economic factors, on the other hand, include quality products, fair prices, and access to resources through cooperative membership. The study employed quantitative research design. It was conducted in the province of Southern Leyte. The province is situated in the southern portion of Leyte Island and includes Limasawa and Panaon Islands. Based on the Cities and Municipalities Competitiveness Index by the National Competitiveness Council through the Regional Competitiveness Committees, Southern Leyte ranked 63rd with its score of 28.41. The ranking is based on the sum of scores on 4 Pillars: Economic Dynamism, Government Efficiency, Infrastructure, and Resiliency. The respondents of the study are the members of the seven large multipurpose cooperatives in Southern Leyte as classified by the Cooperative Development Authority (CDA). There are 255 original number of observations. 15 observations with zero standard deviation were excluded from the analysis. Moreover, 8 observations with more than 15% missing data were also excluded. The total number of observations included in the study is 232. Missing values were treated using mean value replacement (Ringle, Wende, & Will, 2005). The study used PLS-SEM to analyze the data gathered from the survey instrument adapted from the extant literature. The respondents of the study are mostly female (66.67%), married (67.39%), and mainly belonging to 35-44 years old (22.27%); 45-54 years old (28.82%); and 55-64 years old (18.78%). Most are well educated, college graduate (46.93%) and are literate, high school graduate (31.14%). Most of the respondents are employed (60.53%) with a monthly income of less than P9,520 (56.11%) and between P9,520-P19,040 (28.05%). In addition, most of them got their income from salary (62.10%). Findings indicate that economic factors have a significant positive influence on member satisfaction. The direct path coefficient indicates that economic factors positively and significantly influence member satisfaction. This implies that economic benefits that multipurpose cooperative members receive from the cooperative has a significant positive influence on the satisfaction of members. In addition, relationship between economic factors, member satisfaction, and member commitment suggests a significant but small effect of economic factors on member satisfaction, which in turn influences member commitment. This suggests that economic factors indirectly affect member commitment through its influence on member satisfaction. This may indicate that while economic factors themselves may not have a direct and substantial effect on member commitment, they do impact member satisfaction, which in turn affects commitment levels. This work provides actionable insights for managing multipurpose cooperatives (MPCs) with the goal of increasing member commitment. The findings highlight the necessity of promoting member satisfaction through a variety of means, such as enhancing service quality, assuring fair pricing, and providing access to resources. By resolving these issues, MPCs can indirectly increase member commitment, adding to the cooperative's long-term viability and success.